Coping mechanisms adopted by the livestock dependents of drought prone districts of Bihar, India - GOSWAMI, RANDHIR KUMAR; MAITI, SANJIT; GARAI, SANCHITA; JHA, S K; BHAKAT, M; CHANDEL, B S; KADIAN, K S (The Indian Journal of Animal Sciences, 2018)
Coping mechanisms adopted by the farming community has recently become a subject of increasing importance in climate change research with an objective to reduce the vulnerability of climate sensitive people. The present study was designed to identify and assess the coping mechanisms adopted by the livestock dependents to mitigate the impact of drought on their livestock rearing and livelihood security. A total 240 livestock dependents from three drought prone districts of Bihar were interviewed and an exclusively Drought adaptation Index was developed for this study. The study revealed that 49 adaptation strategies were adopted by the livestock dependents which were further distributed into seven broad categories. Most significant coping mechanisms were feeding of extra crop residues, providing frequent extra clean and fresh feed and water, storage of wheat/rice straw, change in cropping pattern, feeding and milking during cool hours, kept animal in shadow, extra bathing of cattle, feeding of extra concentrate, selling of animals and reducing herd size. The study also established that adoption of coping mechanism was increased significantly with the increase in degree of drought proneness and herd size was the most significant contributor to the higher level of adoption of coping mechanisms.